Impact of Brain-Based Teaching on the Conceptual Understanding of Newton's Laws of Motion - Comillo, Rosendo III; Voltaire M. Mistades (Jurnal Pendidikan IPA Indonesia, 2025)
Grounded in cognitive neuroscience, Brain-Based Teaching (BBT) enhances science instruction by aligning classroom practices with how the brain optimally learns and processes information. This mixed-methods study investigated the effectiveness of BBT in improving Grade 8 students' conceptual understanding of Newton's Laws of Motion. Conducted in a public school in Manila, Philippines, the study involved 51 students who participated in an intervention utilizing BBT strategies, including relaxed alertness, orchestrated immersion, and active processing. Quantitative data were collected through a validated 25-item concept test, daily performance worksheets, and a Student Perception of Instruction Questionnaire (SPIQ). Qualitative data came from student journals and semi-structured interviews. Findings showed a significant improvement in post-test scores (M = 9.35), as confirmed by a paired-sample t-test (t(50) = 3.80, p < .001) and a moderate effect size (Cohen's d = 0.67). Daily worksheets consistently received "Very Good" to "Excellent" ratings. One-way ANOVA results revealed significant differences in post-test scores across prior ability levels (F(2, 48) = 10.07, p < .001, η² = .30), suggesting that BBT's effectiveness varied depending on students' initial competence. The SPIQ survey revealed positive perceptions, with the highest mean score (3.6) indicating student satisfaction with the classroom environment and instructional support. Thematic analysis identified three key themes: enhanced instruction through various classroom activities, insightful learning, and retention of learning. Overall, BBT was found to be effective in fostering conceptual understanding and promoting a positive learning environment. Its novelty lies in highlighting the differentiated impact of BBT based on prior achievement in a resource-constrained public school context.